Pengembangan Sistem Informasi Seminar dan Skripsi Mahasiswa - Sabirin, Febrianto; Sulistiyarini, Dewi; Zulkarnain, Zulkarnain (Universitas Hamzanwadi, 2020)
Thesis is the final stage in the lecture process, but there is not yet an adequate system to record the implementation of the thesis at IKIP PGRI Pontianak. This study aims to develop, test the feasibility, and see the user's response from the Seminar and Thesis Information System. The development model used in the development of Seminar, and Thesis Information Systems is ADDIE with research instruments in the form of interviews and questionnaires. Data analysis techniques use descriptive statistics toÂ defineÂ the process of system development, system feasibility, and user response to the system. Seminar and Thesis Information System were developed using HTML, PHP, MySQL and the Bootstrap framework. Users of Seminar and Thesis Information Systems consist of five actors, namely general users, students, examination staff, scheduling staff, and admins. The test results from Information system experts and response from users indicate that Seminar and Thesis Information Systems are in the very good category so that the information system that has been developed can be applied to record the thesis in a real situation in IKIP PGRI Pontianak.